Revision Ulnar Collateral Ligament Reconstruction in Professional Baseball: Current Trends, Surgical Techniques, and Outcomes. Issue 7 (29th July 2019) - Camp, Christopher L.; Desai, Vishal Shwetal; Conte, Stan; Ahmad, Christopher S.; Ciccotti, Michael G.; D'Angelo, John; Griffith, Timothy B.
Objectives: Ulnar collateral ligament (UCL) reconstruction of the elbow is a commonly performed surgery on professional baseball pitchers. Recent reports have suggested that revision rates are on the rise and may be higher than previously thought. The purpose of this study is to provide a comprehensive report on current trends, surgical techniques, and outcomes of revision UCL reconstructions performed on professional baseball pitchers between 2010 and 2016. Methods: The Major League Baseball (MLB) Health and Injury Tracking System (HITS) was used to compile records of all revision UCL reconstructions performed on professional baseball pitchers between 2010 and 2016. Player data and outcomes were obtained from HITS while surgical details were obtained from operative reports. Descriptive statistical analysis was performed on epidemiologic data. Outcomes (return to play rates, return to play times, subsequent injuries, and subsequent surgeries) were compared across the most common surgical techniques (Docking vs. Modified Jobe) and graft sources (palmaris longus autograft vs. hamstring autograft). Results: A total of 69 professional baseball pitchers underwent revision UCL reconstruction from 2010 to 2016 at an average of 1, 424 days (47 months) after their primary surgery. There was a trend toward increasing numbers of revision surgeries over time (R2=0.441; p=0.104). The most commonly used tunnel configuration was the Modified Jobe technique (n=41, 59.4%) and the most common graft utilized was hamstring autograft (n=34, 49.3%). 76.6% of pitchers were able to return to play (RTP) and 55.3% were able to return to the same level of play. Mean time to RTP in players with a palmaris longus autograft was 436 days versus 540 days for hamstring autograft (p=0.108) and the mean time to RTP in players was 423 days for the Docking technique versus 519 days for the Modified Jobe technique (p=0.296). Similar rates of subsequent injuries and surgeries were noted between the two revision techniques and two most commonly used graft constructs. Conclusion: This report detailing revision UCL reconstruction amongst professional baseball pitchers showed a trend towards increasing numbers of revisions being performed, a finding consistent with other recent studies. The overall return to play percentage was higher than previously reported (76.6%); however, significantly fewer (55.3%) players returned to the same level of play. This work also demonstrated decreased return to play times (n=484 days, SD: 117.3) compared to other investigations. The Modified Jobe was the most commonly used surgical technique and the two most commonly used graft constructs were hamstring autograft and palmaris longus autograft. Although this analysis did not reveal any statistically significant comparative differences between surgical techniques or graft constructs, future studies involving head-to-head comparisons of these surgical variables, specific to revision UCL reconstruction, may be helpful in improving player outcomes and career performance.